Implementation of Islamic Social Ethics in the Philosophy of Educational Management Towards Students of Madrasah Trubus Iman Tanah Grogot - Anggi Syahputra Harahap; Kautsar Eka Wardhana; Feby Anggara (Berkah Smart Academica, 2024)
Abstract— The Implementation of Islamic Social Etiquette in the Philosophy of Educational Management is the focal point of investigation within the context of Madrasah Trubus Iman in Padang Pangrapat, Tanah Grogot. This research aims to delve into and analyze how the application of Islamic social etiquette values within the framework of the philosophy of educational management can shape students' characters. The research method employed is qualitative research. Data were obtained through observation, interviews, and document analysis related to educational management in Madrasah Trubus Iman. The research findings indicate that Madrasah Trubus Iman has effectively implemented an educational management approach based on Islamic social etiquette. In the context of integrating Islamic values, such as covering one's aura, avoiding illicit sexual relations, prohibiting unmarried couples from being alone, performing prayers, speaking politely, being obedient to parents, forbidding smoking among adolescents, and greeting fellow Muslims. The positive implications of implementing Islamic social etiquette are not only limited to the aspect of students' character but are also evident in the improvement of the learning atmosphere and interpersonal relationships between students and teachers. Mutual respect and care become crucial points in creating an educational environment that supports holistic student growth. Overall, this research contributes to our understanding of how Islamic social etiquette can be integrated with the philosophy of educational management to create quality Islamic education.